One Less Reason Why: Viewing of Suicide-Themed Fictional Media is Associated with Lower Depressive Symptoms in Youth. Issue 1 (2nd January 2021) - Ferguson, Christopher J.
ABSTRACT: Concerns about whether fictional media can have a contagion effect on youth viewers have been debated for several decades. In the 1980s these led to several lawsuits featuring heavy metal acts as defendants. More recently, concerns have been renewed following the popular television show 13 Reasons Why which depicts an adolescent girl's suicide. The current study examines these concerns in a survey study of 174 youth and their caregivers. Results indicated that, contrary to concerns, viewing suicide themed fictional shows was associated with reduced depressive symptomology and was not associated with suicidal ideation specifically. Depression and suicidal ideation were most associated with experiencing with others' suicides in real life, family environment, bullying and neurotic personality traits. The show 13 Reasons Why specifically was associated with either lower depression or suicidal ideation or null effects, depending on specific outcome. Although correlational, this evidence suggests that suicide prevention efforts should focus less on fictional media and more on prevention of bullying.